In the canyon - Scanlon, Elizabeth Garton (Beach Lane Books, an imprint of Simon & Schuster Children's Publishing Division, 2015)
Illustrations and simple rhyming text present a child who is hiking with a group into the Grand Canyon, enjoying the wonders of nature--whether a lizard, a picture on the stone, or a glimpse of the moon from the bottom.